HKUST‐1 coated piezoresistive microcantilever array for volatile organic compound sensing. (1st November 2013) - Ellern, Ilya; Venkatasubramanian, Anandram; Lee, Jin‐Hwan; Hesketh, Peter; Stavila, Vitalie; Robinson, Alex; Allendorf, Mark
Abstract : The HKUST‐1 metal‐organic framework (MOF) was selected because of the large internal surface area, excellent stability and known properties. Mechanical strain is generated upon the adsorption of analytes into the MOF; it is proportional to concentration and is a function of adsorbed species. Piezoresistive microcantilevers serve as a transduction mechanism to convert surface strain into electrical signals. N‐doped piezoresistive cantilever arrays were fabricated with ten structures per die. Thin films of HKUST‐1 were grown at room temperature using layer‐by‐layer techniques. Dry nitrogen was used as a carrier gas to expose devices to varying concentrations of 12 different volatile organic compounds (VOCs). Results show that stress‐induced piezoresistive microcantilever array sensors with MOF coatings can provide a highly sensitive and reversible sensing mechanism for water vapour and methanol. Characteristic response features allow discrimination based on shape, response time constants and magnitude of response for other VOCs. Devices provided reliable data and proved durable over 18 months of testing. The key advantages of this type of sensor are higher sensitivity with a microporous MOFs, reversible response, α single chip sensing system and low power operation.